Evaluating the immunogenicity of a mouse partial hindlimb for composite allotransplantation - Sun, Jia Hui (Angela); Ligi, Samantha; Biniazan, Felor; Haykal, Siba (Frontiers in Immunology, 2025)
BackgroundVascularized composite allotransplantation (VCA) offers a promising solution for restoring function in patients with severe tissue trauma, yet acute rejection remains a major hurdle. Acute rejection is driven by an immune response against transplanted tissues, requiring lifelong immunosuppression, increasing risks of infections, malignancies, and organ toxicity. This study aims to develop a mouse hindlimb transplant model to investigate immune responses and the phenotype of infiltrating cells in these grafts.Materials and methodsSyngeneic and allogeneic mouse partial hindlimb models were established to evaluate grafted skin and muscle immunogenicity. Male BABL/c and C57BL/6 mice served as donors, C57BL6.sjl mice were recipients. Hindlimbs were procured, including femur, muscle, and skin, and were heterotopically transplanted into recipient mice. Samples were collected at post-operative days 7 (POD7) and 14 (POD14) for histological analysis (H&E staining, immunohistochemistry for CD8, caspase-3, CD31, and TUNEL) to assess cell infiltration, inflammatory T cell presence, apoptosis, and vascularization. Immune cell populations were characterized through flow cytometry.ResultsBoth syngeneic and allogeneic skin and muscle showed increased cellular content at both time points. Allogeneic skin at POD14 exhibited higher cellular content and subclinical rejection, while flow cytometry revealed increased donor-derived and recipient-derived T cells, particularly CD4+ and CD8+ T cells. Additionally, Tr1 cells were more abundant, suggesting a regulatory role in the immune response. Apoptotic markers increased in both grafts at POD14, with more TUNEL-positive cells in allogeneic grafts at POD7. Revascularization, assessed by CD31 expression, was notably present in both syngeneic and allogeneic muscle at POD14.DiscussionThis study provides valuable insights into acute rejection in VCA using a novel mouse hindlimb transplant model. Findings reveal immune response complexity, with increased CD8+ T cells and Tr1 cells in allogeneic skin, and unexpected vascularization in non-vascularized grafts. The rise in Tr1 cells suggests a potential mechanism for immune regulation, offering potential for tolerance induction strategies. These results emphasize the need for tissue-specific immunosuppressive approaches, where targeting Tr1 cells could reduce dependence on broad immunosuppression, improving long-term graft survival and patient outcomes. This work lays the foundation for refining VCA therapies, with more personalized, less toxic immunosuppressive strategies.